2005
DOI: 10.1128/jcm.43.4.1879-1884.2005
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi ospC Heterogeneity among Human and Murine Isolates from a Defined Region of Northern Maryland and Southern Pennsylvania: Lack of Correlation with Invasive and Noninvasive Genotypes

Abstract: B. burgdorferi invasiveness correlates with ospC genotype. To test this hypothesis and whether identical genotypes infect humans and small mammals in specific sites, B. burgdorferi ospC heterogeneity was tested among isolates from northern Maryland and southern Pennsylvania. Six culture-positive patients allowed collection of small animals from their properties, and spirochetes from animals trapped within 300 yards of each patient's home were isolated. 3 ospC sequences were compared to reference sequences. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 33 publications
5
55
2
Order By: Relevance
“…Third, the severe human virulence of B. burgdorferi s.s. is itself evidence for it being a generalist parasite of mammalian hosts, since despite the fact that humans are not its natural reservoir hosts, B. burgdorferi s.s. is capable of invading and infecting the human tissues. Although B. burgdorferi s.s. strains appear to vary in human virulence (Dykhuizen et al 2008;Wormser et al 2008), it has been argued that associations between human pathogenecity and genomic groups are weak and all groups have the potential to cause invasive infections in humans (Alghaferi et al 2005;Jones et al 2006).…”
Section: Maintenance Of Genome Clusters By Frequency-dependent Selectionmentioning
confidence: 99%
“…Third, the severe human virulence of B. burgdorferi s.s. is itself evidence for it being a generalist parasite of mammalian hosts, since despite the fact that humans are not its natural reservoir hosts, B. burgdorferi s.s. is capable of invading and infecting the human tissues. Although B. burgdorferi s.s. strains appear to vary in human virulence (Dykhuizen et al 2008;Wormser et al 2008), it has been argued that associations between human pathogenecity and genomic groups are weak and all groups have the potential to cause invasive infections in humans (Alghaferi et al 2005;Jones et al 2006).…”
Section: Maintenance Of Genome Clusters By Frequency-dependent Selectionmentioning
confidence: 99%
“…Of 118 EM skin biopsy samples in patients from Long Island, NY, 51 (43%) were type A, B, or I, 32 (27%) were type K, and 35 (30%) were other types, but hematogenous dissemination was associated only with types A, B, I, and K (27). In a later study of six B. burgdorferi blood isolates and one skin isolate from patients in Maryland and Pennsylvania, dissemination occurred with these and two other OspC types (H and N) (1). Recently, OspC was shown to bind a tick salivary gland protein, Salp15 (25,26), which is important in establishing early infection in mice (10).…”
mentioning
confidence: 99%
“…The OspC types of human clinical isolates have also been correlated with invasive and non-invasive phenotypes (38,39). However, similar studies demonstrated greater diversity among invasive types than previously recognised, calling into question any causative effect of OspC sequence on invasion (40,41). Carefully controlling for variables other than OspC has not been possible in such studies, since additional genome components of these isolates also differ.…”
Section: Discussionmentioning
confidence: 90%